2021
DOI: 10.1177/1747493021995594
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in stroke incidence and case-fatality rates in Arcadia, Greece: A sequential, prospective, population-based study

Abstract: Background: Stroke incidence and case-fatality are reported to decline in high-income countries during the last decades. Epidemiological studies are important for health services to organize prevention and treatment strategies. Aims: The aim of this population-based study was to determine temporal trends of stroke incidence and case-fatality rates of first-ever stroke in Arcadia, a prefecture in southern Greece. Methods: All first-ever stroke cases in the Arcadia prefecture were ascertained using the same st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Our search of databases and other sources (eFigure 2 in the Supplement) identified 29 221 records, with 463 potentially relevant full-text articles assessed after screening of titles and abstracts. Of these, 49 eligible published studies (eFigure 2 and eTable 3 in the Supplement) reported some data on temporal trend in incidence of stroke at younger ages with ascertainment until at least 1990. The addition of our own data resulted in 50 studies (Table 1 and eTable 4 in the Supplement; 20 prospective population-based studies and 30 based on routinely collected administrative data).…”
Section: Resultsmentioning
confidence: 99%
“…Our search of databases and other sources (eFigure 2 in the Supplement) identified 29 221 records, with 463 potentially relevant full-text articles assessed after screening of titles and abstracts. Of these, 49 eligible published studies (eFigure 2 and eTable 3 in the Supplement) reported some data on temporal trend in incidence of stroke at younger ages with ascertainment until at least 1990. The addition of our own data resulted in 50 studies (Table 1 and eTable 4 in the Supplement; 20 prospective population-based studies and 30 based on routinely collected administrative data).…”
Section: Resultsmentioning
confidence: 99%
“…29 Contrasting our findings, data from the Arcadia Stroke Registry in Greece show stable rates already from 1993 to 2016. 30 Data from Auckland, New Zealand 31 and Dijon, France 10 imply increasing incidence rates in young adults. Notably, authors of the Dijon Stroke Registry reported an increase in the incidence of first-ever AIS in 18-to 55-year-old adults from 1985 to 2007, but thereafter, the rates remained stable International Journal of Stroke, 18 (4) until the end of the study in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting our findings, data from the Arcadia Stroke Registry in Greece show stable rates already from 1993 to 2016. 30…”
Section: Discussionmentioning
confidence: 99%
“…The burden of stroke in the last decade in Greece fluctuates widely across different regions with an annual stroke incidence ranging from 117 to 534 cases per 100,000 inhabitants [2][3][4]. Despite almost 35,000 patients suffering and 16,000 dying from stroke annually in Greece [1,5], the management in the acute phase of stroke remains heterogeneous.…”
Section: Introductionmentioning
confidence: 99%